The Role of Self-Motivation in Self-Regulated Learning - Wangid, Muhammad Nur (Universitas Ahmad Dahlan, 2022)
Studies on self-regulated learning (SRL) have been well-established and draw education and psychology researchers. This paper focuses on self-motivation as an important element of self-regulated learning. Self-motivation is the first stage an individual needs before acting and determining the success of his/her act. Self-motivation encompasses self-efficacy, intrinsic interest, goal orientation, outcomes expectations, and activation of knowledge. This correlational study involved 100 randomly recruited guidance and counseling department students. The data were collected using self-motivation and self-regulated learning scales and analyzed using regression analysis. This study showed that not all aspects of self-motivation play important roles in self-regulated learning. Goal orientation was found to be the most influential aspect, followed by self-efficacy, activation of knowledge, outcomes expectations, and intrinsic interest/value. This result implies that the learning goal may serve as a strong motivating factor in self-regulated learning. Self-efficacy may invoke psychological energy that drives individuals to perform self-regulated learning. The process and its rationalization are discussed further in this paper